(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Nitella zamanii has been described and illustrated as a new species from a rice field at Charghat upazila in Bangladesh. The new species resembles Nitella furcata and N. polycarpa but differs by presence of accessory branchlets, spiky dactyls and size of oogonium, oospore and antheridium. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21358 Bangladesh J. Plant Taxon. 21(2): 181-185, 2014 (December)